The role of web engineering in e-learning application development: a review study - Mohd Ali, Hussin Ahmad Hamzah; Abu Seman, Muhamad Sadry (Institute of Advanced Engineering and Science (IAES), 2022)
Web engineering is a growing multidisciplinary paradigm that has hardly begun to curiosity the interest, researchers, and other key actors involved in developing web-based systems. Therefore, the effect of web engineering applications on e-learning systems should be investigated to guarantee that the web’s potential for supporting the learning process is appropriately used. The objective of the study highlights the advantages, benefits, and contributions of web engineering in developing e-learning systems. This is qualitative research. The primary data was collected via an in-depth study of pertinent research studies. The second tool was an interview with the e-learning systems developers. The results showed that the most influential web engineering tools to develop e-learning systems. Moreover, the main areas of development of e-learning systems include changing the learning environment characteristics, changing student behaviour, changing roles, and incorporating artificial intelligence (AI). The results also showed that web applications' main challenges in e-learning systems include technologies, adaptability, lack of experience and training, lack of funding, changing student preferences and needs, the gap between the mobile and computer versions, and security threats, job-overload, and time. It was found that web engineering has a significant role in developing e-learning applications.